2015
DOI: 10.1155/2015/718975
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 and ARG-1 Concentrations in Bone Marrow and Peripheral Blood of Metastatic Neuroblastoma Patients Do Not Associate with Clinical Outcome

Abstract: The expression of the immunosuppressive molecules IL-10 and arginase 1 (ARG-1), and of FOXP3 and CD163, as markers of regulatory T cells (Treg) and macrophages, respectively, was evaluated in bone marrow (BM) and peripheral blood (PB) samples collected at diagnosis from patients with metastatic neuroblastoma (NB). IL-10 and ARG-1 plasma concentrations were measured and the association of each parameter with patients' outcome was tested. The percentages of immunosuppressive Treg and type-1 regulatory (Tr1) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…In contrast, the percentage of both Treg and Tr1 cells was significantly lower in NB patients (0.34 § 0.11 and 0.07 § 0.019, respectively) than in healthy children (1.09 § 0.16 and 1 § 0.27, respectively) (p D 0.0056 and p < 0.0001), reflecting the observations in the BM samples. These data, obtained in a larger number of PB samples from NB patients and controls than our previous report, 10 confirmed the lower percentage of PB Tr1 cells and suggested that the higher percentage of PB Treg previously reported was inaccurate due to the small sample size.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, the percentage of both Treg and Tr1 cells was significantly lower in NB patients (0.34 § 0.11 and 0.07 § 0.019, respectively) than in healthy children (1.09 § 0.16 and 1 § 0.27, respectively) (p D 0.0056 and p < 0.0001), reflecting the observations in the BM samples. These data, obtained in a larger number of PB samples from NB patients and controls than our previous report, 10 confirmed the lower percentage of PB Tr1 cells and suggested that the higher percentage of PB Treg previously reported was inaccurate due to the small sample size.…”
Section: Resultssupporting
confidence: 90%
“…8 Treg cells have been previously characterized in peripheral blood (PB) from very small cohorts of NB patients. [9][10][11] A higher percentage of Treg in NB patients than healthy children was reported by us and Tilak et al, whereas Gowda et al showed that their number was similar in lowand high-risk patients.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Interestingly, implantation of NB cells was also associated with increased serum levels of the anti‐inflammatory cytokine IL‐10. Increased IL‐10 levels are a typical finding for some types of NB and have been associated with metastatic disease …”
Section: Discussionmentioning
confidence: 99%
“…27 Finally, anti-NB functions of T lymphocytes may be suppressed by high levels of T regulatory cells in NB patients. 28 …”
Section: Introductionmentioning
confidence: 99%